Multisensory development - Bremner, Andrew J.; Lewkowicz, David J.; Spence, Charles (Oxford : Oxford University Press, 2012)
We perceive and understand our environment using many sensory systems-vision, touch, hearing, taste, smell, and proprioception. Yet how do we develop the ability to integrate these senses? This book is unique in exploring this extraordinary feat of human nature.
Description based on online resource; title from home page (viewed on July 13, 2012).
Includes bibliographical references and index.
Keywords: Senses and sensation; Perception; Neurophysiology; Cognitive neuroscience